2010
DOI: 10.1038/ijir.2009.64
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone, SHBG and cardiovascular health in postmenopausal women

Abstract: Cardiovascular disease (CVD) affects men and women differently with women having a lower incidence and later onset of disease. Research has recently refocused interest on the cardiovascular role of androgens. The purpose of this review is to summarize the evidence available on the association between testosterone and cardiovascular health in postmenopausal women. Published studies relating testosterone and sex hormone-binding globulin (SHBG) to CVD and its risk factors were reviewed. Studies included in this r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
53
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 145 publications
5
53
0
3
Order By: Relevance
“…Some studies have reported that high testosterone is associated with an adverse CVD risk factor profile in postmenopausal women, irrespective of polycystic ovary syndrome. 3,124 Polymorphism of the (CAG)n repeat of the AR gene was associated with CVD and risk factor profiles in postmenopausal women. 125 Thus far, evidence is lacking for an association of testosterone with CVD events in women, and it is uncertain whether testosterone could be used as a postmenopausal hormone therapy.…”
Section: Testosterone Deficiency and Cvd In Womenmentioning
confidence: 99%
“…Some studies have reported that high testosterone is associated with an adverse CVD risk factor profile in postmenopausal women, irrespective of polycystic ovary syndrome. 3,124 Polymorphism of the (CAG)n repeat of the AR gene was associated with CVD and risk factor profiles in postmenopausal women. 125 Thus far, evidence is lacking for an association of testosterone with CVD events in women, and it is uncertain whether testosterone could be used as a postmenopausal hormone therapy.…”
Section: Testosterone Deficiency and Cvd In Womenmentioning
confidence: 99%
“…Menopause is the transitional period after which the ovaries stop producing eggs, and there is a cessation of menstruation. During this period the levels of both estrogens and androgens are lower than in premenopausal women due to follicular depletion and age-related atrophy of the adrenal cortex (35).…”
Section: Rationale and Significance Of The Studymentioning
confidence: 99%
“…However, the postmenopausal ovaries remain hormonally active, secreting significant amounts of androgens (35). In women with bilateral salpingo-oophorectomy (BSO), which is the surgical removal of the ovaries, the levels of androgens are lower than in women with natural menopause (36,37).…”
Section: Rationale and Significance Of The Studymentioning
confidence: 99%
See 2 more Smart Citations